1999
DOI: 10.2500/105065899782102908
|View full text |Cite
|
Sign up to set email alerts
|

The Forgotten Turbinate: The Role of the Superior Turbinate in Endoscopic Sinus Surgery

Abstract: The fate of the middle turbinate in endoscopic sinus surgery has been a subject of debate for some time. The superior turbinate's role, however, has been largely passed over. Past anatomic descriptions and illustrations have given surgeons the incorrect impression that this structure is well superior and out of the field of dissection. Injury to the superior turbinate may account for postoperative hyposmia. The superior turbinate also serves as a constant landmark for the sphenoethmoidal recess, and a limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 5 publications
1
48
1
3
Order By: Relevance
“…A p value < 0.05 was accepted as statistically significant. referred to the superior turbinate as a reliable anatomical landmark of the sphenoid sinus and its natural ostium [2,13,15,16,18]. Most reports state that the natural ostium of the sphenoid sinus is positioned medial to the superior turbinate [2,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A p value < 0.05 was accepted as statistically significant. referred to the superior turbinate as a reliable anatomical landmark of the sphenoid sinus and its natural ostium [2,13,15,16,18]. Most reports state that the natural ostium of the sphenoid sinus is positioned medial to the superior turbinate [2,16].…”
Section: Discussionmentioning
confidence: 99%
“…Orlandi et al [18] reported on the use of the superior turbinate as a constant, reliable landmark for the natural ostium of the sphenoid sinus. When the posterior por-…”
Section: Discussionmentioning
confidence: 99%
“…These turbinates originate from the ethmoid bone. The superior turbinate has the common attachment of the middle turbinate to the skull base [ 39 ]. The supreme turbinate may be found in up to 65 % of specimens [ 9 ].…”
Section: Superior and Supreme Turbinates And Meatusesmentioning
confidence: 99%
“…In 1999, a group of eminent rhinologists from a number of American centres published two articles to describe a technique for identiWcation of the superior turbinate and utilizing it as a landmark in endoscopic posterior ethmoidectomy and sphenoidotomy [2,4] Although this was more than a decade ago, there have not been, to the best of our knowledge, any further articles conWrming or contradicting the operative experience of the above group. There have been, however, several articles presenting cadaveric and/or radiological studies of the superior turbinate [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 97%
“…The authors of the current article have routinely used the technique published in 1999 [2,4] for identiWcation of the superior turbinate, and relying upon it as a landmark during endoscopic surgery involving the posterior ethmoid and sphenoid sinuses. In addition, we have further modiWed the technique by attempting to identify the two parts of the basal lamella of the superior turbinate.…”
Section: Introductionmentioning
confidence: 99%